Carbon Sequestration - Sarvajayakesavalu, Suriyanarayanan; Karthikeyan, Kannan (IntechOpen, 2022)
Global climate change is intensifying and is increasingly recognized as a major challenge that requires an urgent response from scientists and other communities. Reducing the emission of greenhouse gases, especially carbon dioxide, is an essential process to mitigate climate change. This book addresses the latest carbon management approaches that will combat the increasing levels of carbon dioxide in the atmosphere. It provides a comprehensive review of the physical, chemical, and biological processes of carbon sequestration. Chapters discuss carbon capture, storage, utilization, and chemistry, as well as the geomechanical aspects of carbon sequestration.